This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Let f : ( 0 , ∞ ) → R , Consider the function as f ( α ) = 2 α 1 − 1 ∫ ∞ sinh ( π α x ) x 2 − 1 d x = x = cosh ( t ) 2 α 1 − 0 ∫ ∞ sinh ( π α cosh ( t ) ) d t = 2 α 1 − 0 ∫ ∞ [ π α cosh ( t ) 1 + 2 π α cosh ( t ) k = 1 ∑ ∞ π 2 k 2 + π 2 α 2 cosh 2 ( t ) ( − 1 ) k ] d t = u = α sinh ( t ) π 2 0 ∫ ∞ k = 1 ∑ ∞ k 2 + α 2 + u 2 ( − 1 ) k − 1 d u . Here we have used the pole expansion of c s c h and the elementary integral ∫ 0 ∞ s e c h ( t ) d t = 2 π . Since the partial sums of the remaining alternating series (with terms decreasing in absolute value) are bounded by the first term, i. e. the integrable function u ↦ 1 + α 2 + u 2 1 , the dominated convergence theorem allows us to interchange summation and integration. We obtain f ( α ) = π 2 k = 1 ∑ ∞ ( − 1 ) k − 1 0 ∫ ∞ k 2 + α 2 + u 2 d u = k = 1 ∑ ∞ k 2 + α 2 ( − 1 ) k − 1 for α > 0 . The series on the right-hand side converges uniformly on R , so it defines a continuous function of α on R . We can write, α → 0 + lim f ( α ) = α → 0 + lim k = 1 ∑ ∞ k 2 + α 2 ( − 1 ) k − 1 = k = 1 ∑ ∞ k 2 + 0 2 ( − 1 ) k − 1 = k = 1 ∑ ∞ k ( − 1 ) k − 1 = lo g ( 2 ) Thus, our problem can be solved by observing that 3 α 3 2 − 3 α 4 π 1 ∫ ∞ sinh 2 ( π α x ) x 2 − 1 x cosh ( π α x ) d x = − 3 α 4 f ′ ( α ) = 3 4 k = 1 ∑ ∞ ( k 2 + α 2 ) 3 / 2 ( − 1 ) k − 1 ⟶ α → 0 + 3 4 k = 1 ∑ ∞ k 3 ( − 1 ) k − 1 = 3 4 η ( 3 ) = ζ ( 3 ) .